Custom and Retail Exempt Meat Processing - Chad Carr; Larry Eubanks; Ryan Dijkhuis (EDIS)
AN204, a 4-page fact sheet by Chad Carr, Larry Eubanks, and Ryan Dijkhuis, explains the exemptions for custom and retail exempt meat processors, and also covers Florida Sunshine Law specific to meat processors. Published by the UF Department of Animal Science, September 2008.